A regional study of the genus Phyllopsora (Ramalinaceae) in Asia and Melanesia - Sonja Kistenich; Mika Bendiksby; Charles Santhanaraju Vairappan; Gothamie Weerakoon; Siril Wijesundara; Patricia A. Wolseley; Einar Timdal (2019)
Phyllopsora is a crustose to squamulose lichen genus inhabiting the bark of trees in moist tropical forests and rainforests. Species identification is generally challenging and is mainly based on ascospore morphology, thallus morphology and anatomy, vegetative dispersal units, and on secondary chemistry. While regional treatments of the genus have been conducted for Africa, South America and Australia, there exists no study focusing on the Asian and Melanesian species. Previously, 24 species of Phyllopsora s. str. have been reported from major national studies and checklists representing 13 countries. We have studied herbarium material of 625 Phyllopsora specimens from 18 countries using morphology, anatomy, secondary chemistry, and molecular data to investigate the diversity of Phyllopsora species in Asia and Melanesia. We report the occurrence of 28 species of Phyllopsora including the following three species described as new to science: P. sabahana from Malaysia, P. siamensis from Thailand and P. pseudocorallina from Asia and Africa. Eight species are reported as new to Asia. A key to the Asian and Melanesian species of Phyllopsora is provided.